(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the main trends in contemporary Karakalpak prose literature. It explores thematic, stylistic, and ideological developments in modern prose, focusing on issues such as national identity, social transformation, and individual experience. The study also highlights the influence of globalization and literary innovation on Karakalpak writers.